Respuesta :
2/3 (6c + 9d) + 3/4 (8c - 16d) = -18
We are solving for c when d = -2
Substitute D: 2/3 (6c + 9(-2)) + 3/4 (8c - 16(-2)) = -18
Solve parentheses, multiply fraction with parentheses: 2/3 (6c -18) + 3/4 (8c + 32) = -18
Combine like terms: 4c - 12 + 6c + 24 = -18
Subtract 12 from both sides: 10c + 12 = -18
Divide by 10: 10c = -30
ANSWER: c = -3
We are solving for c when d = -2
Substitute D: 2/3 (6c + 9(-2)) + 3/4 (8c - 16(-2)) = -18
Solve parentheses, multiply fraction with parentheses: 2/3 (6c -18) + 3/4 (8c + 32) = -18
Combine like terms: 4c - 12 + 6c + 24 = -18
Subtract 12 from both sides: 10c + 12 = -18
Divide by 10: 10c = -30
ANSWER: c = -3
Answer:
- c = - 3
-----------------------------------
Simplify the equation by distribution, then substitute the value of d and solve for c:
- 2/3(6c + 9d) + 3/4(8c - 16d) = - 18
- 2/3(6c) + 2/3(9d) + 3/4(8c) - 3/4(16d) = - 18
- 4c + 6d + 6c - 12d = - 18
- 10c - 6d = - 18
- 10c - 6(-2) = - 18
- 10c + 12 = - 18
- 10c = - 12 - 18
- 10c = - 30
- c = - 3